Evolution and Cell Physiology. 1. Cell signaling is all of biology - Torday, John S. (American Physiological Society, 2013)
I hypothesize that the First Principles of Physiology (FPPs) were co-opted during the vertebrate transition from water to land, beginning with the acquisition of cholesterol by eukaryotes, facilitating unicellular evolution over the course of the first 4.5 billion years of the Earth's history, in service to the reduction in intracellular entropy, far from equilibrium. That mechanism was perpetuated by the advent of cholesterol in the cell membrane of unicellular eukaryotes, ultimately giving rise to the metazoan homologs of the gut, lung, kidney, skin, bone, and brain. Parathyroid hormone-related protein (PTHrP), whose cognate receptor underwent a gene duplication during the transition from fish to amphibians, facilitated gas exchange for the water-to-land transition, since PTHrP is necessary for the formation of lung alveoli: deletion of the PTHrP gene in mice causes the offspring to die within a few minutes of birth due to the absence of alveoli. Moreover, PTHrP is central to the development and homeostasis of the kidney, skin, gut, bone, and brain. Therefore, duplication of the PTHrP receptor gene is predicted to have facilitated the molecular evolution of all the necessary traits for land habitation through a common cellular and molecular motif. Subsequent duplication of the β-adrenergic receptor gene permitted blood pressure control within the lung microvasculature, allowing further evolution of the lung by increasing its surface area. I propose that such gene duplications were the result of shear stress on the microvasculature, locally generating radical oxygen species that caused DNA mutations, giving rise to duplication of the PTHrP and β-adrenergic receptor genes. I propose that one can determine the FPPs by systematically tracing the molecular homologies between the lung, skin, kidney, gut, bone, and brain across development, phylogeny, and pathophysiology as a type of “reverse evolution.” By tracing such relationships back to unicellular organisms, one can use the underlying principles to predict homeostatic failure as disease, thereby also potentially forming the basis for maneuvers that can treat or even prevent such failure.